Glucocorticoid prescribing habits of sports medicine physicians working in high-performance sport: a 30-nation survey. Issue 7 (5th February 2020) - Hughes, David; Vlahovich, Nicole; Welvaert, Marijke; Tee, Nicolin; Harcourt, Peter; White, Susan; Vernec, Alan; Fitch, Ken; Waddington, Gordon
Abstract : Objectives: Glucocorticoids are commonly prescribed in medicine. When administered via certain routes, glucocorticoids are prohibited for incompetition use by WADA. The glucocorticoid prescribing habits of sports medicine doctors have not been reported. Methods: An online survey was distributed internationally to physicians working in high-performance sports. The survey queried the doctors about their use of glucocorticoids with athletes and their understanding of WADA's regulations regarding glucocorticoid use in competition. Results: 603 sports medicine doctors from 30 different countries participated. The majority (>85%) routinely injected glucocorticoids and/or prescribed glucocorticoids by other routes. There were substantial differences in the common routes of injection as well as types of glucocorticoid used among the physicians from various countries. A relatively small percentage of sports doctors (<25%) accurately identified which routes of glucocorticoid administration are prohibited in competition by WADA. There was a great variation in how long before competition the use of glucocorticoids would cause the doctor to consider applying for a therapeutic use exemption (TUE). A better understanding of the clearance rates of glucocorticoids from athletes' bodies would greatly aid sports medicine doctors' decisions on how and when to apply for a TUE. A small number of doctors had observed side effects of glucocorticoid administration, with the majority of side effects being minor in nature. Conclusion: Glucocorticoids are widely prescribed by sports physicians. There is a need to better educate sports physicians on the current WADA regulations in relation to glucocorticoid administration.